Modifikasi Alat Perajang Batang Singkong (Rabakong Tipe Tep 5) untuk Meningkatkan Kapasitas Kerja - Asmara, Sandi; Kuncoro, Sapto; Suharyatun, Siti; Setiawan, Firnando Anggi (abe.fp.unila.ac.id, 2023)
Lampung Province is the largest producer of cassava in Indonesia. However, cassava production in Lampung has been declining over the past five years due to many farmers switching to other commodities due to the long harvesting period and unstable prices. This has resulted in a buildup of cassava stem waste, requiring innovation to manage this waste. Hence, the cassava stem chopper (Rabakong) was introduced. Rabakong has been developed by Agricultural Engineering (TEP) students from the University of Lampung, starting from TEP 1, TEP 2, TEP 3, TEP 4, and TEP 5. This research method involves modifying the frame of the previous version, redesigning the components to be modified using AutoCAD software, and then fabricating and collecting data after modification. The latest modified Rabakong machine underwent significant changes in the number of blades, which are fewer but arranged spirally for efficiency in chopping and space-saving. The working capacity has increased to 207 kg/hour at 1400 rpm. Waste material has decreased to 11.39%. Fuel consumption is 2.580 liters/hour. The percentage of finely chopped materials (<0.2 mm) is only 17.19%, while coarsely chopped materials (>0.5 cm) reach 51.41%, indicating that the latest version is more suitable for coarse results.. Keywords: Cassava Stems, Design, Efficiency, Modification.